Phytochemistry, Medicinal Chemistry & In-vitro Cytotoxicity of Ipomoea nil and Gloriosa superba - Goel, Bharat (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Phytochemistry; Medicinal Chemistry; in-vitro Cytotoxicity; Ipomoea Nil; Gloriosa Superba